Ćwiczenia i sport - wyzwania i korzyści dla dzieci i młodzieży z cukrzycą typu 1 - Szadkowska, Agnieszka (Pediatric Endocrinology Diabetes and Metabolism, 2021)
Regular physical activity is able to replace almost every drug, but all drugs taken together will not replace exercise. This statement was written in XVI century by Wojciech Oczko (1537–1599) royal doctor of Polish Kings. Despite medical advances over 500 years, this sentence is still relevant today. In the hundred years since the discovery of insulin, enormous progress has also been made in the pharmacological treatment of type 1 diabetes mellitus (T1DM). In the last decades new formulations of insulin, new methods of insulin delivery, e.g., advanced closed-loop hybrid systems have significantly improved glucose control. However, we must remember that good glycemic control is a key, but not one factor in preventing the development of chronic diabetes complications. Regular physical activity is associated with greater insulin sensitivity, increased  fitness,  better lipid profile and blood pressure [1]. It extends remission duration in children with new onset diabetes mellitus [2]. It significantly decreases risk of premature cardiovascular morbidity and all-cause mortality. Regular physical activity has not only health but also social benefits for children and adolescents with diabetes mellitus, so it is one of the fundamental parts of diabetes management and should be encouraged [3].